STIMULASI METODE TIME OUT DALAM MENERAPKAN SIKAP DISIPLIN ANAK USIA DINI - Mega Cahya Dwi Lestari (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2020)
The time out method is effective in stimulating discipline in early childhood. The success factor of the time-out method can be found in the age difference that causes different stages of development in each child which includes cognitive development, moral development, discipline, and the consistent role of parents and teachers in the implementation of the correct time-out procedure, especially the provision of rewards following aim. Disciplinary education needs to be instilled in children from an early age that if children make mistakes they will certainly receive consequences, for this reason, the punishment function in children's education. Discipline is a behavioral value that can be done by force and can be done voluntarily. In early childhood, this form of discipline must be implemented voluntarily and through play. Teachers, the community, and parents are the most influential factors in disciplining children.